Influence of vortex vein engorgement for photodynamic therapy in central serous chorioretinopathy - Seongyong Jeong; Wonki Kang; Min Sagong (Scientific Reports, 2024)
Abstract This study evaluates the efficacy of photodynamic therapy (PDT) in treating central serous chorioretinopathy (CSC) based on the number of engorged vortex vein draining macula visualized on ultra-widefield (UWF) indocyanine green angiography (ICGA). Thirty-six eyes of 36 patients with treatment-naïve CSC were included. Macula-draining vortex veins were assessed in each quadrant using UWF ICGA. The resolution of subretinal fluid (SRF), pigment epithelial detachment (PED), ellipsoid zone (EZ) disintegrity, and retinal pigment epithelium (RPE) irregularity were evaluated at 3 months after PDT. Visual and anatomical improvements were monitored for 12 months. Logistic regression analysis was performed to identify factors associated with poor visual outcomes. A higher number of macula-draining vortex vein was associated to persistent SRF (p = 0.004), PED (p = 0.001), EZ disintegrity (p = 0.011), and RPE irregularity (p = 0.001). Macula-draining vortex veins were also correlated with poor EZ restoration and limited best corrected visual acuity (BCVA) improvements. In multivariate analysis, the number of macula-draining vortex vein (B = 0.197, p = 0.047) was a risk factor for worse BCVA at 12 months. Increased macula-draining vortex vein was related with unfavorable anatomical and poor visual outcomes after PDT in CSC patients.